1990
DOI: 10.1016/0010-0285(90)90015-v
|View full text |Cite
|
Sign up to set email alerts
|

A theory of comparative response times and “difference” judgments

Abstract: In two experiments, subjects performed three tasks: First, they learned associations between names of hypothetical persons and adjectives that described them. Second, they judged "differences" in likeableness between pairs of names. Third, they pressed one of two keys to indicate which person of each pair was more (or less) likeable. Response times showed the traditional distance effect, end effect, and semantic congruity effect. A simple model was developed to describe response times and "difference" ratings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 22 publications
2
112
3
Order By: Relevance
“…Alternatively, according to differential bias theories of the SCE (Birnbaum & Jou, 1990;Link, 1990Link, , 1992Schwarz & Stein, 1998), this effect rises as a consequence of a dynamic, strategic adjustment of decisional criteria within an evidence accrual decision process (i.e., a random walk). For example, if the instruction is to choose the smaller stimulus and the stimulus pair contains a very small stimulus, bias theories assume that individuals recognize that this stimulus is likely to be the correct choice and lower the decision criterion associated with the accumulation of evidence for that stimulus (or conversely, recognize that this stimulus is unlikely to be the correct choice when the instruction is to choose the larger and raise that same decision criterion; see also Link, 1992, pp.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, according to differential bias theories of the SCE (Birnbaum & Jou, 1990;Link, 1990Link, , 1992Schwarz & Stein, 1998), this effect rises as a consequence of a dynamic, strategic adjustment of decisional criteria within an evidence accrual decision process (i.e., a random walk). For example, if the instruction is to choose the smaller stimulus and the stimulus pair contains a very small stimulus, bias theories assume that individuals recognize that this stimulus is likely to be the correct choice and lower the decision criterion associated with the accumulation of evidence for that stimulus (or conversely, recognize that this stimulus is unlikely to be the correct choice when the instruction is to choose the larger and raise that same decision criterion; see also Link, 1992, pp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors found a contextual effect; this change of process occurs only when the gambles are of the form (x, p; 0), where all x Ͼ 0 or all x Ͻ 0 and few values were at or near zero. Birnbaum and Jou (1990) presented a model of choice response times to describe three major phenomena of choice response times: the distance effect, the end effect, and the semantic congruity effect. The distance effect refers to the fact that it takes less time to choose between two stimuli that are farther apart in subjective value.…”
Section: Buying and Selling Prices: Viewpoint Or Endowment?mentioning
confidence: 99%
“…Both models correctly imply changes of rank order between buying and selling prices. As noted by Leth-Steensen and Marley (2000) in reference to Birnbaum and Jou (1990), it can be difficult to distinguish effects of bias parameter from those attributed to the evaluation process. A critical test between these interpretations has not yet been conducted.…”
Section: Choice Response Times and Configural Weightingmentioning
confidence: 99%
“…Indeed, semantic congruity effects have been observed not only in magnitude comparisons involving objects, but also in judgments of preferential choice. For example, Birnbaum and Jou (1990) found that judging which individual is ''liked more'' for generally likeable individuals took less time than judging between unlikeable individuals, whereas judging which individual is ''liked less'' for likeable individuals took more time than judging between unlikeable individuals (also Nagpal & Krishnamurthy, 2008). The mechanisms instantiated in the BARTlet model may well prove applicable to decision making in areas such as consumer choice and social judgment.…”
Section: Reference Points In Magnitude Comparisonsmentioning
confidence: 99%